Profiles of Odorant Specific Performance in Olfactory Testing. Issue 1 (January 2023) - Schlosser, Rodney J.; Soler, Zachary M.; Mace, Jess; Farrell, Nyssa; Rimmer, Ryan; Alt, Jeremiah A.; Ramakrishnan, Vijay R.; Edwards, Thomas S.; Smith, Timothy L.
Background: Olfactory dysfunction (OD) can occur from a variety of etiologies. However, there are few reports examining whether varying etiologies have unique profiles of psychophysical testing that may provide insight into the pathophysiology of OD. Methods: Adults with chronic rhinosinusitis with and without nasal polyps (CRSwNP/CRSsNP) and healthy control adults with no sinus complaints underwent olfactory assessment with Sniffin' Sticks. Profiles of identification and discrimination were compared between CRS and non-CRS subjects across the spectrum of OD. Results: Normosmics with or without CRS identified apple, pineapple, and turpentine less frequently than expected (range 52%-68% correct). Hyposmics with CRS correctly identified orange more frequently than control hyposmics (83%-93% vs 68% for controls) with similar findings for rose. Hyposmics of all cohorts were unable to identify apple (26%). Discrimination profiles were similar across the spectrum of OD and between diagnostic groups. Conclusions: Identification and discrimination rates of specific odorants may provide unique information regarding the etiology of OD, however psychophysical testing is a complex interplay of olfactory and trigeminal function, the strength of target odorant, distractor choices, and familiarity with odorants.